Melanogenesis Inhibitory Activity, Chemical Components and Molecular Docking Studies of Buch.-Ham. D. Don. Flowers - Nateelak Kooltheat PhD; Aman Tedasen PhD; Kenshi Yamasaki MD, PhD; Moragot Chatatikun PhD (SAGE Publishing, 2023)
Safe depigmenting agents are currently increasing in the cosmetic or pharmaceutical industry because various compounds have been found to have undesirable side effects. Therefore, the present study aimed to investigate the melanogenesis inhibitory effects of Prunus cerasoides Buch. -Ham. D. Don. flower extracts and their molecular mechanism in B16F10 mouse melanoma cells. Moreover, we also examined phenolic and flavonoid contents, antioxidant activity, chemical constituents of potential extracts, and molecular docking. The highest phenolic and flavonoid contents with the greatest scavenging activity were found in the butanol extract of the P. cerasoides flower compared to other extracts. From all extracts, only crude, diethyl ether, and butanol extracts showed an inhibition of mushroom tyrosinase activity, cellular tyrosinase activity, and melanin content as well as the downregulation of the gene expression of the microphthalmia-associated transcription factor (MITF), tyrosinase, tyrosinase-related protein-1 (TRP-1), and tyrosinase-related protein-2 (TRP-2) in α-MSH-stimulated B16F10 cells. Based on the molecular docking study, n-hexadecanoic acid, heptadecanoic acid, octadecanoic acid, 9,12-octadecadienoic acid, 9,12,15-octadecanoic acid, and eicosanoic acid might show an inhibitory effect against tyrosinase and MITF. In conclusion, this finding demonstrates that both the diethyl ether and butanol extracts of the P. cerasoides flower can effectively reduce tyrosinase activity and melanin synthesis through the downregulation of the melanogenic gene expression in B16F10 cells and through the molecular docking study. Taken together, the diethyl ether and butanol extracts of the P. cerasoides flower could be an anti-melanogenic ingredient for hyperpigmentary or melasma treatment.